Edukasi Pemanfaatan Teknologi Ramah Lingkungan untuk Pengelolaan Air Limbah Rumah Tangga di Kampung Cibunut Kelurahan Kebon Pisang Kota Bandung Tahun 2021 - Iing Rustandi; Gilang Permana; Dila Syarifah Nur Fadhilah (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Environmental pollution is now a major problem in the development of science. The problem of water pollution is one of the impacts of the development of science itself. The development of environmentally friendly technology for wastewater treatment towards waste-free production is an important step in maintaining environmental sustainability. Household wastewater produced from various sectors has the potential to pollute the environment if not handled properly. The purpose of this community service is to discuss the importance of utilizing environmentally friendly technology in managing household wastewater towards waste-free production. The use of environmentally friendly technology is the main solution in dealing with household wastewater problems, with the potential to create new economic opportunities. To achieve waste-free production, cooperation is needed between the government, industrial sector, academics, and the community. At the household level, at the micro level, it is currently still lacking to meet the need for clean water due to an inadequate waste disposal system. There needs to be design innovation to minimize the impact of environmental water pollution, one of the simple environmentally friendly technologies for treating wastewater is Constructed Wetland (CW) technology. The application of Constructed Wetland (CW) for household wastewater treatment in Cibunut Village, Kebon Pisang Subdistrict, Bandung City using ornamental plants Iris (Iris pseudoacorus), Water Jasmine (Echinodorus palaefolius) and a combination of both for 2 months, showed that the combination of plants was able to reduce COD, TSS and BOD better than single plants, with efficiencies reaching 95%, 94% and 85% respectively.